Perspectives on Functional Red Mold Rice: Functional Ingredients, Production, and Application - Yanli, Feng; Xiang, Yu (Frontiers in Microbiology, 2020)
Monacolin K is a secondary metabolite of the Monascus species that can inhibit cholesterol synthesis. Functional red mold rice (FRMR) is the fermentation product of Monascus spp., which is rich in monacolin K. FRMR is usually employed to regulate serum cholesterol, especially for hypercholesterolemic patients who refuse statins or face statins intolerance. The present perspective summarized the bioactive components of FRMR and their functions. Subsequently, the efficient strategies for FRMR production, the future challenges of FRMR application and the possible directions were proposed. This perspective helps to understand the present situation and developmental prospects of FRMR.